1991
DOI: 10.1037/0012-1649.27.3.421
|View full text |Cite
|
Sign up to set email alerts
|

Continuity and discontinuity in infant negative and positive emotionality: Family antecedents and attachment consequences.

Abstract: This study was based on the premise that much of the instability evident in research on infant emotionality/temperament is a function not so much of measurement error (as typically presumed) but lawful discontinuity. Infants who changed from high to low and from low to high levels of negative or positive emotionality between 3 and 9 months of age were compared with infants who remained stable during the period on distal measures of the family environment (prenatally and neonatally measured) and proximal measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
160
3
7

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(178 citation statements)
references
References 59 publications
8
160
3
7
Order By: Relevance
“…Higher levels of child fear and irritability and lower levels of effortful control were related to higher initial levels of rejection and inconsistent discipline. These relations are consistent with the findings of previous studies that demonstrated relations between temperament and parenting (e.g., Bates et al, 1995;Belsky et al, 1991;Halverson & Deal, 2001;Kochanska et al, 2000;Malatesta & Haviland, 1986). However, when the mutual prediction of changes in temperament and parenting was examined, a more specific pattern emerged, and each temperament variable had a distinct pattern of relations with parenting.…”
Section: Nih-pa Author Manuscriptsupporting
confidence: 92%
“…Higher levels of child fear and irritability and lower levels of effortful control were related to higher initial levels of rejection and inconsistent discipline. These relations are consistent with the findings of previous studies that demonstrated relations between temperament and parenting (e.g., Bates et al, 1995;Belsky et al, 1991;Halverson & Deal, 2001;Kochanska et al, 2000;Malatesta & Haviland, 1986). However, when the mutual prediction of changes in temperament and parenting was examined, a more specific pattern emerged, and each temperament variable had a distinct pattern of relations with parenting.…”
Section: Nih-pa Author Manuscriptsupporting
confidence: 92%
“…Few investigators have directly addressed the problem of the infiuence of infant negative emotionality on the developing attachment relationship; the studies by Belsky, Fish, and Isabella (1991) and Crockenberg (1981) are notable exceptions. Second, few if any investigators have experimentally manipulated the aspect of behavior called maternal sensitivity, which in attachment theory is deemed crucial for the development of a secure attachment bond.…”
Section: Discussionmentioning
confidence: 99%
“…The development of secure attachment, which can act as a basic protective system, is considered an indicator of a satisfactory interaction throughout the first year of life (Belsky, Fish & Isabella, 1991;Cerezo, Trenado & Pons-Salvador, 2012). According to various studies carried out in the United States and Europe, in the non-clinical population the percentage of children with secure attachment is 67 %, while 33 % have insecure attachment (Brisen, 2002 for a review).…”
Section: Discussionmentioning
confidence: 99%